Poop for thought: Can fecal microbiome transplantation improve cognitive function in aging dogs? - Curtis Wells Dewey (Open Veterinary Journal)
Canine cognitive dysfunction (CCD) is the dog version of human Alzheimer's disease (AD), bearing strikingly similar pathological features with this neurodegenerative disorder. The gastrointestinal system is in constant communication with the brain via several conduits collectively termed the gut-brain axis. The microbial population of the gut, called the microbiota, has a profound effect on interactions that transpire along this communication route. Recent evidence suggests that dysbiosis, or an abnormal gut microbial population, is linked to cognitive impairment in rodent AD models and human AD. There is also evidence from rodent AD models that correcting dysbiosis by transferring fecal material from healthy donors to the gastrointestinal tracts of cognitively impaired recipients (fecal microbiome transplantation, or FMT) reverses AD-associated brain pathology and improves cognitive function. Though limited, there are some clinical reports of FMT improving cognitive function in human AD. The goals of this review article are to provide an overview of the mechanisms involved in dysbiosis-associated cognitive decline and how FMT may play a role in therapy for such decline. Additionally, a potential role for FMT in CCD is discussed. [Open Vet J 2025; 15(2.000): 556-564]